Causes and Prevention of Global Diseases Sexually Transmitted Infections: Literatur Review - Fitriansyah, Aidil; Juliandini, Erlin; Eviheriyanto, Eviheriyanto; Olivianti, Gustri; Puput Ari Susanto, Wahyu; Hasyim, Hamzah (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2023)
Sexually transmitted infections (STIs) are a group of infections that are currently responsible for many morbidities and mortality in developing countries, because STIs have a role in facilitating the transmission of human immunodeficiency virus (HIV) and have a significant negative impact on reproductive health and children. Complications of STIs can cause infertility in both men and women, ectopic pregnancy, cervical cancer, premature death, congenital syphilis, low birth weight, prematurity and ophthalmia neonatorum. In developing nations, sexually transmitted infections (STIs) remain a significant issue due to their high incidence and prevalence. To prevent these issues, efforts to control and prevent STIs are required. In addition to the lack of diagnostic tools for services, rising antibiotic resistance, shifting patterns of STI pathogens, low treatment seeking behavior, and complex transmission dynamics, the lack of political policies to control STIs is fundamental to the limited success of STI control in developing nations. Invest in effective control measures and to maintain and strengthen the basic health system; however, there is a lack of data on the prevalence of diseases and the effectiveness of programs. Primary prevention and a variety of treatment options are some general strategies that can be used to prevent and control STIs in developing nations. Programs for changing behavior, structural interventions, and the use of a variety of prevention technologies are all examples of primary prevention interventions.